Early Treatment of Hepatitis C Virus Improves Health Outcomes and Yields Cost-Savings: A Modeling Study in Argentina - Elgart, Jorge Federico (2022)
OBJECTIVE: Most untreated hepatitis C virus (HCV) patients develop chronic infection and severe complications, including death. Direct-acting antivirals in early stages of liver fibrosis reduce complications and healthcare costs. However, therapy is often delayed, and patients in early stages have limited access to effective treatments. We assessed the clinical and economic effect of treating chronic HCV at early versus late stages of disease in Argentina. METHODS: A Markov model of the natural HCV history was used to forecast lifetime liver-related and economic outcomes from social security sector perspective. Healthcare use and transition probabilities were drawn from literature. Demographic characteristics of the patients and treatment attributes were based on data from registrational trials of glecaprevir/pibrentasvir. RESULTS: Lower rates of all hepatic complications and liver-related mortality were predicted when treatment was initiated in mild versus advanced disease. Sustained virologic response rates were similar among all stages. Higher quality-adjusted life years (QALYs) were predicted when treatment was initiated in mild (F0-F1) versus moderate (F2-F3) or advanced (F4) liver disease (11.5, 9.9, and 7.5 QALYs, respectively). Delaying treatment increased long-term total lifetime costs (F4: AR$ 1 437 816; F2-F3: AR$ 967 673; F0-F1: AR$ 954 018; 37.10 AR$=1 USD, Nov 2018 exchange rate) and provided fewer QALYs. CONCLUSIONS: Our study show early treatment was a dominant strategy compared with treatment in advanced stages of liver disease. These results may help health policy makers take actions to reduce health and economic burden of HCV in Argentina.